Rabbit Skin Gelatine Effect Towards Yoghurt Quality - Pancapalaga, Wehandaka; Ashari, Bagus (Food Science and Technology Journal (Foodscitech), 2020)
This research aims to discover the quality of yoghurt added by rabbit skin gelatine of various concentrations. Qualities measured are protein content, fat content, acidity, pH, water holding capacity (WHC), syneresis, viscosity, and yoghurt texture. Materials used in this research are skim milk, rabbit skin gelatine, and yoghurt culture, which consisted of bacteria such as L. bulgaricus, S. thermophilus, and L. Acidophilus. The experiment is conducted using Completely Randomised Design, consisted of four treatments and five-time repetition. If there is an effect, the treatment later continued to Duncan's Multiple Range Test. Experimentation on texture is conducted through an organoleptic test with 25 panellists and later analysed with the Kruskal-Wallis Test. The treatments determined in this experiment are the effect on the addition of rabbit skin gelatin proportion of 0% (P0), 0.4% (P1), 0.6% (P2), and 0.8% (P3). The result of the Analysis of Variance (ANOVA) shows that the addition of gelatine has a significant difference (P<0.05) towards protein content, water holding capacity (WHC), and syneresis and no significant difference (P>0.05) towards the fat content, viscosity, pH, and yoghurt's acidity degree. The Kruskal-Wallis test result shows the significant difference (P>0.05) towards yoghurt's texture. This research concludes that the best yoghurt quality is obtained by the addition of 0.8% of rabbit skin gelatine.